KOMPETENSI PENGEMBANGAN PROFESI DAN POLA PEMBINAAN GURU BIDANG STUDI GEOGRAFI SMA NEGERI SE EKS KARESIDENAN PATI - Apik budi Santoso; Erni Suharini; Sriyono Sriyono (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2017)
In order to achieve the objectives of the National Education educating the nation and develop the whole person is needed role professional educators. In accordance with the Law of the Republic of Indonesia No. 20 Year 2003 on National Education System, the position of teachers as educators are professional positions. Development of teacher competency standards aimed at improving the quality of teachers and teacher development patterns in a structured and systematic. However, the reality on the ground needs to be studied more in depth whether the teachers have been able to improve the competence of their professional development and how development patterns regarding the agencies or other competent parties. The population is all Geography teacher who has been certified and teach in high schools in Pati residency Ex se, but the data information obtained by means of random sampling. Variables include teacher professional development competence variable Geography and development patterns related to geography teacher professional development competencies. Data collection using documents, questionnaires and interviews. While data analysis using descriptive analysis percentage.The results showed that: 1) the research subjects have had a long teaching experience, have all been certified thus formally as a professional teacher. Professional development activities that stand turned out to be activities of the new book, student work activities (LKS). In MGMPs rides, teachers often team up matter for LKS material. Competence is quite encouraging professional development is the productivity of the preparation of papers, preparation of props Although there has been an increase in productivity of academic scholarly side in supporting the development of the profession, but in general (71.00%) level of competence of their professional development is still far from ideal, 2) pattern coaching competence Geography teacher professional development in SMA se Ex Pati residency, in the form of in-house training, discussions, workshops have been conducted by the teachers of Geography. However, other activities such as internships, partnerships with other schools and distance learning has not been optimally implemented either by the government (Kemendikbud, District Education Office, LPMP) and profider / other competent parties. So generally coaching competency Geography teacher professional development in the study area is not patterned in a clear and steady.Suggestions put forward related to this include: a). need to change the paradigm that every teacher to achieve keprofesinalannya level should be supported by scientific work, not just teaching and a pass UKG and graduated as a teacher learners, b). teachers need to be encouraged ability / competence development profession with appreciation and / reward (it may include funding), in order to awaken the passion attitudes and behavior as a professional teacher, c). the schools and other government agencies as well as to always earnestly reprogrammed professional development activities of teachers in a structured time and funding.